Empirical Study on Bretton Woods Twins – World Bank and IMF: Understanding the roles and scope of the Bretton Woods Twins (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In 1944, the Bretton Woods Agreement established a new international monetary system. The creation of the International Monetary Fund (IMF) and the World Bank were two of its most enduring legacies. The World Bank and the IMF, often called the Bretton Woods Institutions, are twin intergovernmental pillars supporting the structure of the world’s economic and financial order. Both have taken on expanding roles, and there have been renewed calls for additional expansion of their responsibilities, particularly in the continuing absence of a single global monetary agreement. The two institutions may seem to have confusing or overlapping functions. However, while some similarities exist (see the following figure), they are two distinct organizations with different roles. While both the World Bank and International Monetary Fund, are two separate entities, often not clear the role of each of them is therefore that this paper seeks to consolidate diverse information reviewed from both entities with the purpose of being able to understand the functioning and scope of each of these important institutions that have had successes and setbacks and ultimately have an active role in global finance and economy, despite the many detractors who are at levels world. There is an anecdote, which is worth mentioning. “John Maynard Keynes, recognized at the inaugural meeting of the International Monetary Fund was confused by the names he thought the Fund should be called a bank, and the World Bank should be called a bottom. Confusion has reigned ever since. The Bank and the IMF are two intergovernmental pillars supporting the structure of economic and financial world”. The fundamental difference between the two is understood as the Bank institution primarily for the development, while the IMF is a cooperative institution that seeks to maintain an orderly system of payments and receipts between nations. The manner followed to choose the head of each organization has a different procedure, but the important thing is that in the next few years, several countries such as Brazil, India have more participation that is active.